Computational Study on Structural Behaviour of Cold-Formed Steel Built-Up I-Section Beams - Sari, Nur Azrinna; Koh Heng Boon (Recent Trends in Civil Engineering and Built Environment, 2024)
Cold-formed steels are usually applied in pairs to achieve increased moment stability and bearing performance. This paper presents the finite element analysis (FEA) on buckling behavior of cold-formed steel built-up I-section beams. The I-beams were built up using back-to-back cold-formed plain channel sections. Two series of beams with single and double rows of bolts with 5 different end restraints were modeled using LUSAS FEA software. The plain channels were modelled as 3D surface elements and the bolts were assigned as joint with rotational stiffness. The beams were subjected to 4-point bending and buckling analysis were carried out to determine the buckling mode and the capacity. From the FEA, single and double rows of cold-formed built-up I-section beams performed almost the same buckling behavior. The beams with the supports of lateral end restraint (translation in z) and fully fixed had shown significant increment of the buckling capacity compared with beams with simply supported. Overall, end restraint plays an important role in the cold formed built-up beams.